2023
DOI: 10.3390/ph16121698
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally Important Pro-Health Active Ingredients and Antioxidant Properties of Fruits and Fruit Juice of Selected Biennial Fruiting Rubus idaeus L. Cultivars

Mirosława Chwil,
Renata Matraszek-Gawron,
Mikołaj Kostryco
et al.

Abstract: Raspberry fruits are an important source of many biologically active chemical compounds exerting nutritional and pro-health effects. The study presents a comparative analysis of nutritionally important bioactive chemical compounds—polyphenols; flavonoids, including anthocyanins; vitamin C; amino acids; fatty acids; and primary metabolites—contained in the fruits of three biennial fruiting cultivars, R. idaeus ‘Glen Ample’, ‘Laszka’, and ‘Radziejowa’, i.e., common cultivars in Poland and Europe. The antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
1
0
0
Order By: Relevance
“…However, these values are about five times higher than those found for the samples analyzed in the present study [47]. At the same time, the raspberry extracts investigated in this study exhibited a stronger ferric-reducing power than that found by Chwil et al [48], who investigated the antioxidant potential of the extracts from fruits of three cultivars, such as R. idaeus 'Glen Ample', 'Laszka', and 'Radziejowa' (cultivated in Poland); they found a reducing power similar to the cultivar R. idaeus 'Heritage', R. innominatus, and R. niveus, but it was lower than R. caucasicus × Chester, R. cyri, and R. insularis [49,50].…”
Section: Antioxidant Activitycontrasting
confidence: 85%
“…However, these values are about five times higher than those found for the samples analyzed in the present study [47]. At the same time, the raspberry extracts investigated in this study exhibited a stronger ferric-reducing power than that found by Chwil et al [48], who investigated the antioxidant potential of the extracts from fruits of three cultivars, such as R. idaeus 'Glen Ample', 'Laszka', and 'Radziejowa' (cultivated in Poland); they found a reducing power similar to the cultivar R. idaeus 'Heritage', R. innominatus, and R. niveus, but it was lower than R. caucasicus × Chester, R. cyri, and R. insularis [49,50].…”
Section: Antioxidant Activitycontrasting
confidence: 85%